The role of serum lactate dehydrogenase / pleural fluid adenosine deaminase ratio and cancer ratio plus in the diagnosis of malignant pleural effusion: A retrospective study - Vu-Hoai, Nam; Nguyen-Huu, Hoa; Nguyen-Dang, Khoa; Tran-Le, Quoc-Khanh; Duong-Minh, Ngoc; Tran-Ngoc, Nguyen; Le-Thuong, Vu (Acta Biomedica Atenei Parmensis, 2025)
Background: While serum LDH to pleural fluid ADA ratio (sLDH/pADA) and CRp, as calculated by dividing sLDH/pADA by the percentage of pleural fluid lymphocytes, show potential in identifying malignant pleural effusion (MPE), their diagnostic value in tuberculosis-endemic countries remains unclear. Aims: This study assessed their utility in distinguishing MPE among patients with exudative pleural effusion (PE). Methods: This retrospective study was conducted at Department of Pulmonary Medicine, Cho Ray Hospital (Vietnam) from January 2023 to June 2024, including patients with PE who met the inclusion criteria. All patients underwent blind pleural biopsy or pleural fluid cellblock analysis to confirm or exclude MPE. Clinical, laboratory, and pleural fluid data were collected. The optimal cut-off values, AUC, sensitivity, and specificity of sLDH/pADA and CRp were calculated to diagnose MPE. Results: 204 patients with exudative PE were classified into MPE (n=119, 58.3%) and non-MPE (n=85, 41.7%) groups. Compared to the non-MPE group, patients with MPE were older, had higher serum LDH, sLDH/pADA, and CRp (all p <0.05). They also had a lower pleural neutrophil ratio and ADA (all p <0.05). For sLDH/pADA, the optimal cut-off value was 20, yielding an AUC of 0.85 with 85% sensitivity and 79% specificity. For CRp, the optimal threshold was 18, corresponding to an AUC of 0.72, 73% sensitivity, and 58% specificity. Conclusion: sLDH/pADA showed high sensitivity and good diagnostic value for identifying MPE, while CRp did not enhance accuracy. The findings support sLDH/pADA as a useful tool for distinguishing MPE, especially in tuberculosis-endemic regions.